People living with HIV display increased anti-apolipoprotein A1 auto-antibodies, inflammation, and kynurenine metabolites: a case–control study - Frias, Miguel A.; Pagano, Sabrina; Bararpour, Nasim; Sidibé, Jonathan; Kamau, Festus; Fétaud-Lapierre, Vanessa; Hudson, Peter; Thomas, Aurélien; Lecour, Sandrine; Strijdom, Hans; Vuilleumier, Nicolas (Frontiers in Cardiovascular Medicine, 2024)
Objective: To study the relationship between autoantibodies against apolipoprotein A1 (anti-apoA1 IgG), human immunodeficiency virus (HIV) infection, antiretroviral therapy (ART), and the tryptophan pathways in HIV-related cardiovascular disease.This case-control study conducted in South Africa consisted of control volunteers (n=50), people living with HIV (PLWH) on ART (n=50), and untreated PLWH (n=44).Cardiovascular risk score, vascular measures, and an extensive biochemical characterization (routine, metabolomic and inflammatory systemic profiles) were recorded.Methods: Anti-apoA1 IgG levels were assessed by in-house ELISA. Inflammatory biomarkers were measured with the Meso Scale Discovery® platform kynurenine pathway metabolites measured using targeted metabolomic profiling performed by LC-MRM/MS.Results: Cardiovascular risk and vascular measures were similar, while important differences in systemic inflammatory and tryptophan pathways were observed between the 3 groups. Anti-apoA1 IgG seropositivity was 15%, 40% and 70% in control volunteers, PLWH-ART experienced and PLWH-ART naïve groups, respectively. Circulating anti-apoA1 IgG were significantly negatively associated with CD4+ counts and positively associated with viremia and pro-inflammatory biomarkers (IFNɣ, TNFα, MIPα, ICAM-1, VCAM-1). While circulating anti-apoA1 IgG were associated with increased levels of kynurenine in both control volunteers and PLWH, the kynurenine/tryptophan ratio was significantly increased in PLWH ARTtreated.HIV infection increases the humoral response against apoA1 which is associated with established HIV severity criteria and kynurenine pathway activation.